История больницы Св. Евфросинии в Глухове - Назарова, В.В.; Мирошниченко, А.Н. (Сіверщина в історії України, 2021)
В статье на основании архивных документов и периодических
изданий XIX века сделана попытка максимально подробно реконструировать историю открытия и функционирования больницы
Св. Евфросинии в городе Глухове Черниговской губернии. Данное
лечебное учреждение было основано и содержалось на средства
семьи Терещенко. В работе освещены все этапы возникновения
данной больницы, начиная с момента приобретения Терещенко
участка земли, на котором в последствии будет располагаться
больница, и заканчивая ее переименованием в 1918 году. Большое
внимание уделено строительству здания больницы и дальнейшей
ее работе на протяжении 40 лет: с 1878 по 1918 год. Большинство использованных в исследовании материалов вводится в научный оборот впервые. У статті була зроблена спроба максимально докладно реконструювати історію відкриття та функціонування лікарні Св. Єфросинії в місті Глухові Чернігівської губернії. Цей лікувальний заклад є одним з найстаріших в місті. Лікарня була відкрита у 1879 р. Заснована родиною
Терещенків, утримувалась їх коштом, розташовувалась у їх будівлі. Наразі пам’ятка історії «Безплатна лікарня св. Єфросинії» (охоронний номер 2246-См) знаходиться на території Національного заповідника «Глухів» в історичному центрі міста на Києво-Московській вулиці. Ця будівля має історичну цінність як об’єкт, пов’язаний з благодійною діяльністю
відомих українських промисловців і меценатів Терещенків. Крім того, це
зразок історичної забудови міста другої половини XIX ст.
Докладного дослідження історії лікарні досі не проводилося. Всі відомі згадки лікарні про неї в науковій літературі були вельми короткими.
Вони стосувалися лише приблизного датування часу спорудження будівлі,
фінансової участі в цьому проєкті родини Терещенків або мали мемуарний характер. У даній роботі детально висвітлені всі етапи виникнення
і функціонування лікарні Св. Єфросинії. У статті велику увагу приділено передісторії відкриття цього лікувального закладу, перипетій заснування та будівництва приміщення лікарні. Наводиться інформація про членів піклувальної ради і медичний персонал.
Робота написана на основі фактів, взятих з архівних документів і
мало вивчених періодичних видань ХІХ ст. Більшість використаних в дослідженні матеріалів вводяться до наукового обігу вперше. An attempt was made in the article to reconstruct the history of the opening
and functioning of the hospital of St. Euphrosyne in the city of Glukhov,
Chernigov province, in as much detail as possible. This medical institution is
one of the oldest in the city. Opened in 1879, the hospital was founded and
supported by the Tereshchenko family. The building of the former hospital of
St. Euphrosyne is located on the territory of the National Reserve «Glukhov»
in the historical center of the city on Kiev-Moskovskaya Street. It is an architectural
monument of local importance and has security number 2246. This
building has a historical value as a monument associated with the charitable
activities of famous Ukrainian industrialists and patrons of the arts Tereshchenko,
and is an example of the historical buildings of the city in the second
half of the 19th century. A detailed study of the history of the hospital has not
yet been carried out. All known references to St. Euphrosyne’s hospital in the
scientific literature have been very brief. They concerned only the approximate
dating of the construction of the hospital building, the financial participation of
the Tereshchenko family in this project, or had a memoir in nature. This work
covers in detail all the stages of the emergence and functioning of the St. Euphrosyne
Hospital. The article focuses on the prehistory of the opening of this
clinic, the vicissitudes of its establishment and the construction of the hospital
building itself. Provides information about the members of the Board of
Trustees and the hospital’s medical staff. The work was written on the basis
of archival documents and little-studied periodicals of the 19th century. Most
of the materials used in the research are being introduced into scientific circulation
for the first time.